Menumbuhkan Kemampuan Berbahasa Anak Desa Sukanagara melalui Kegiatan Literasi dan Interaksi Sehari-hari - Hana Nurhasanah; Elysa Febriyanti; Fiqri Abdul Muqit; Yuni Ertinawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to improve the speaking skills of elementary school students in Sukanagara Village, Tasikmalaya Regency through the application of the show and tell method. The background of the study stems from the problems of low student self-confidence, limited vocabulary, and passive participation when asked to speak in front of the class. The research method used is Classroom Action Research (CAR) which was carried out in two cycles with a descriptive qualitative approach. Data collection was carried out through observation, documentation, and field notes focused on four indicators of speaking skills, namely fluency, courage, pronunciation, and vocabulary use. The results of the study showed a significant increase in students' speaking skills, from 31.25% at the initial condition to 93.75% at the end of Cycle I, and reaching 100% in Cycle II. In addition, students appeared more confident, more courageous in expressing opinions, and were able to construct sentences more appropriately according to the context. Thus, the show and tell method has proven effective in creating an active, enjoyable learning atmosphere and is able to optimally improve students' speaking skills.